2016
DOI: 10.1016/j.seizure.2016.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Refractory status epilepticus and autoimmune encephalitis with GABA A R and GAD65 antibodies: A case report

Abstract: Autoimmune encephalitis associated with GABAAR and GAD65 antibodies might be a severe and refractory disease. The appropriate treatment is currently unknown for those patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 4 publications
1
8
0
Order By: Relevance
“…Despite medical interventions, our patient experienced a relapse within 4 months, which is consistent with Gagnon et al's report [ 10 ] of a patient with AE with anti-GABA A R and antiglutamate decarboxylase 65 antibodies who endured severe relapses. It is therefore plausible that AE with multiple antineuronal antibodies is relapse-prone.…”
Section: Discussionsupporting
confidence: 92%
“…Despite medical interventions, our patient experienced a relapse within 4 months, which is consistent with Gagnon et al's report [ 10 ] of a patient with AE with anti-GABA A R and antiglutamate decarboxylase 65 antibodies who endured severe relapses. It is therefore plausible that AE with multiple antineuronal antibodies is relapse-prone.…”
Section: Discussionsupporting
confidence: 92%
“…Multiple antibody positivity associated with cancer has been reported in several studies [182, 183]. Petit-Pedrol et al (2014) recently reported five cases of anti-GABA A R and anti-GAD65 antibodies co-occurring in CSF and serum [17], and a single case report of a female with encephalitis was found to harbor anti-GABA A R and anti-GAD65 antibodies in CSF and serum [184]. Other double antibody positivity combinations that have been identified are anti-NMDAR and anti-GAD antibodies [185], anti-NMDAR and anti-D2R [165, 186], anti-GABA B R and anti-Hu [187], and anti-Caspr2 and anti-Lgi1 in a patient with Morvan syndrome [188].…”
Section: Potential Mechanisms Of Double Autoantibody Positivitymentioning
confidence: 99%
“…Notwithstanding, this patient suffered from seizure recurrences upon withdrawal of the therapy underscoring the fact that the appropriate duration for immunosuppressive therapy in patients with autoimmune encephalitis is unknown. [ 15 ]…”
Section: Discussionmentioning
confidence: 99%